1996
DOI: 10.1080/10408399609527730
|View full text |Cite
|
Sign up to set email alerts
|

Applications of magnetic resonance imaging in food science

Abstract: The physical and chemical changes that occur in foods during growth, harvest, processing, storage, preparation, and consumption are often very difficult to measure and quantify. Magnetic resonance imaging (MRI) is a pioneering technology, originally developed in the medical field, that is now being used in a large number of disciplines to study a wide variety of materials and processes. In food science, MRI techniques allow the interior of foods to be imaged noninvasively and nondestructively. These images can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 66 publications
0
27
0
Order By: Relevance
“…Long T1 or T2 values indicate slow relaxation whereas short T1 or T2 values indicate fast relaxation. The T1 and T2 are equal in the case of water and some dilute solutions [13]. Difference in the relaxation times is exploited to highlight different sections within a particular biological material.…”
Section: Nmr Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Long T1 or T2 values indicate slow relaxation whereas short T1 or T2 values indicate fast relaxation. The T1 and T2 are equal in the case of water and some dilute solutions [13]. Difference in the relaxation times is exploited to highlight different sections within a particular biological material.…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…3 Schematic diagram of a mass spectroscopy set up [19] can be at such a fundamental level that researchers can study processes at the molecular level. Specific examples of the use of NMR spectroscopy in foods can be found from several excellent sources [12,13,[23][24][25][26][27][28][29][30][31]. Following are the generalized form of diverse applications of NMR in food analysis:…”
Section: Ion Source Samplementioning
confidence: 99%
“…A review of MRI application to food products is reported by Schmidt et al . (), Ruan & Chen () and Marcone et al . ().…”
Section: Introductionmentioning
confidence: 97%
“…Magnetic resonance imaging (MRI) technique was first developed as a non-destructive method for use in medical research and diagnosis, and the applications of the MRI technique in the field of food science has increased since the last decade (Schmidt & Lai, 1991;Schmidt, Sun, & Litchfield, 1996;Webb, Belton, Gil, & Delgadillo, 2001). The major advantages of MRI are:…”
Section: Introductionmentioning
confidence: 98%